Development of oxide composite materials for cathode element of IT-SOFCs - Susanto, Iwan; Kamal, Dianta Mustofa; Rahmiati, Tia; Rizkia, Vika; Zainuri, Fuad; Belyamin, Belyamin; Permana, Sulaksana; Subardi, Adi; Fu, Yen-Pei (Eastern-European Journal of Enterprise Technologies, 2022)
Investigating the properties of composite oxide for intermediate temperature solid oxide fuel cells (IT-SOFCs) has been done as a new cathode material. Using a solid-state reaction method, the metallic oxide material has been employed to create the composite model system. During the sintering process, a model system of Sm0.5Sr0.35Ba0.15FeO3-δ (SSBF15) was constructed. Thermal gravimetric analysis (TG) was played to utilize the oxygen content and weight loss of the model. In the meantime, the structure of the composite was characterized using X-ray diffraction (XRD), and the conductivity properties were tested by thermal conductivity. The structural design was made possible by the findings, which revealed that the composite model structure exhibited the crystalline structure with perovskite phase. Weight losses during the construction of the structure were reflected in the decomposition and evaporation of the composite’s constituent parts. After the calcination process up to 950 °C, the model system’s formation oxygen content was obtained of 2.94 in 800 °C. The electrical conductivity maximum obtained in 12.2 S·cm-1 at 430 °C. At low temperatures, the conductive behavior was affected by the metallic element, while at higher temperatures, it was influenced by the ionic structure. As a result, mixed ionic and electric conductors (MIEC) were extensively utilized in the process of generating the conductive properties. The SSBF15 composite has a good chance of being used as an alternative cathode material with a perovskite single phase for future IT-SOFCs applications based on the structure and conductivity results. Additional testing and observation are required to determine the resistance’s value when incorporated into the electrolyte and its heat expansion properties